Smart Water Level Leakage Detection System - Mahale, Amol Vasant; Nikam, Tushar Prakash; Jadhav, Nikita Eknath; Mayekar, Hritik Prasad; Gholap, P. S. (International Journal of Recent Advances in Multidisciplinary Topics, 2022)
Water is one of the most important natural resource essential for survival. This paper focuses on leakage detection in over-ground pipes as well as sprinkler pipes and location method based on vibration sensors to overcome the problems of water dispersion in water distribution networks. Bearing in mind that water leakage is a big issue that has already grown to become a critical issue in agricultural area. The main objective of the paper is to show the work which is done on a water monitoring and leakage detection system using some basic components: Flow sensor, GPRS module, Solenoid valve, Microcontroller, Solenoid valve and relays.